2016
DOI: 10.5455/javar.2016.c-172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiogram of Salmonella species isolated from poultry products in Ebonyi State, Nigeria

Abstract: Objective: This study evaluated the occurrence and antimicrobial susceptibility profile of Salmonella species isolated from various poultry products including chicken meat, poultry eggs, poultry bird's drinking water, and poultry feed. Materials and methods: A total of 79 samples comprising of chicken meat (n=20), egg shell (n=15), poultry egg contents (n=18), drinking water (n=14), and poultry feed (n=12) were bacteriologically and microscopically analyzed for the isolation of Salmonella species. Results: Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…were susceptible to ciprofloxacin (82.72%), gentamicin (77.27%), norfloxacin (81.82%), and streptomycin (79.09%) [7,14,18,31]. On the contrary, this finding is incompatible with the findings of several researchers, among them Ifeanyichukwu et al [39] presented the data where isolated Salmonella spp. were found to be highly resistant to gentamycin, and Paul et al [7] showed the data where ciprofloxacin was susceptible against merely 20% Salmonella isolates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…were susceptible to ciprofloxacin (82.72%), gentamicin (77.27%), norfloxacin (81.82%), and streptomycin (79.09%) [7,14,18,31]. On the contrary, this finding is incompatible with the findings of several researchers, among them Ifeanyichukwu et al [39] presented the data where isolated Salmonella spp. were found to be highly resistant to gentamycin, and Paul et al [7] showed the data where ciprofloxacin was susceptible against merely 20% Salmonella isolates.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is compatible with the studies by many researchers [5,14,31,32]; however, Islam et al [18] showed that the isolated Salmonella spp. were highly sensitive and Ifeanyichukwu et al [39] revealed as highly resistant to amoxicillin, and Akbar and Anal presented that the isolated Salmonella spp. from ready-to-eat poultry were highly susceptible to erythromycin [3].…”
Section: Discussionmentioning
confidence: 99%
“…The method of Bashir, 2017 was adopted. The prevalence rate employed was 20 % (Ifeanyichukwu et al, 2016) and the formula for the sample size determination is shown below (Bashir, 2017):…”
Section: Samples Sizementioning
confidence: 99%
“…The genus Salmonella was first recovered from intestinal samples of infected pigs (classic swine fever) by Theobald Smith in 1855 and colleagues, but was named after the American bacteriologist, D. E. Salmon, a co-worker of Theobald Smith (Arora and Arora, 2014). Although, the contamination of poultry farms and production lines (Agbaje et al, 2010;Adesiyun et al, 2014;Agada et al, 2014a;Agada et al, 2014b;Ifeanyichukwu et al, 2016;Akeem et al, 2017;Bashir, 2017;Nidaullah et al, 2017), but recent findings revealed that the prevalence thereby was still at relatively low level when compared to the commercial raw poultry carcass exposed to unhygienic retailing materials and environments because of the improved environmental sanitation, hygiene, disease treatment of most commercial poultry farms (Babatunde et al, 2017). Therefore, this study investigated the occurrence of Salmonella in commercial raw chicken meat from their retailing equipment and environments within some open markets in Southern Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of resistance varies globally, but the resistance rate is on the rise (Ifeanyichukwu et al, 2017;Louden et al, 2012;Mąka et al, 2015;Velasquez et al, 2018). To better understand the resistance mechanisms, it is necessary to detect antimicrobial resistance genes in Salmonella isolated from retail meats.…”
mentioning
confidence: 99%